THE IDEOLOGY IN THE INDONESIAN-ENGLISH TRANSLATION OF CULTURAL TERMS (English Education Journal, 2015)
This study deals with the translation of cultural terms found in Andrea Hirata’s novel Laskar Pelangi into The Rainbow Troops. The aims of the study were to describe the cultural terms category found in the novel, to find the most frequently translation technique applied by the translator in translating the cultural terms, and to analyze the ideology of translation applied by the translator in translating the novel. The study used was a qualitative descriptive method. The result of the study showed that the most frequently translation technique applied is compensation (18.08%). It can be concluded that the translation ideology used by the translator is domestication ideology. It could be concluded that by applying this domestication ideology, the translator made the foreign-sounding languages and cultures found in the Laskar Pelangi novel, transparent to the target language reader with something equal and equivalent, so the work of translation is acceptable, and easy to understand.